Dragon Pet - Avatar, Ari (New York, NY Scholastic Inc., 2023)
"It's time for another field trip! Ari and his class visit a farm where they are entrusted with an egg to adopt. This is a big responsibility for Ari but he's excited nonetheless. Everyone's egg hatches into harmless animals, except for Ari's. His hatches into a baby dragon! Cool, right? Wrong! As the dragon grows, Ari realizes he may have bitten off more than he can chew. Ari and his friends have to figure out a way to capture the dragon before it destroys all of Blockhaven! Can they handle it?"--
"An Unofficial Roblox Book."
112416
Keywords: Roblox (Computing platform) -- Fiction; School field trips -- Fiction; Farms -- Fiction; Eggs -- Fiction; Dragons -- Fiction; Pets -- Fiction; Humorous stories; Humorous fiction; Fiction